No room for Chiang Kai-shek in contemporary Taiwan? Qujianghua: The removal of Chiang’s legacy from the Taiwanese landscape after the 1990s and its reactions - Ho, Ryan Qixu (Nanyang Technological University, 2020)
Beginning in the 1990s, the DPP and other pro-democracy activists, together with the reformist faction of the GMD under President Lee Teng Hui, began to remove references to former leader Chiang Kai-shek from public life, commonly known as Qujianghua (去蒋化), a term first used by the Taiwanese media in the 1990s.The DPP administrations under President Chen Shui-bian and President Tsai Ing-wen aggressively promoted Qujianghua during their term, much to the chagrin of the opposition GMD. Although the DPP administrations under both Chen and Tsai portrayed it as a milestone in Taiwanese democracy, the GMD views it as a political attack on its historical legitimacy. The Transitional Justice Bill passed by Taiwanese lawmakers on 5th December 2017 spelled the end of sites associated with Chiang Kai shek’s name in Taiwan. The renaming of streets and schools which bear his name has also been made compulsory for the first time under Taiwanese law.